Behavioural response of breeding Mute Swans Cygnus olor to lockdown measures: a case study - Włodarczyk, Radosław (Wildfowl, 2024)
In spring 2020, human activity was strongly reduced because of restrictions in movements imposed during the Covid-19 pandemic. In Poland, traditional recreational areas and tourist attractions were closed to the public from 24 March to 20 April 2000, which coincided with the time when Mute Swan Cygnus olor pairs establish their breeding territories. Following withdrawal of the restrictions at the end of April, people’s access to the countryside in May and June returned to normal levels. This study compares the breeding performance of Mute Swans at two distinct locations which differ in the level of human activity: a private fish farm closed to the public vs. a dam reservoir which is open to visitors. Fishponds at the Sarnów fish farm are visited on a regular basis only by workers at the site (5–6 people per day), whereas Sulejowski Reservoir is a popular recreational area, especially during weekends, for hundreds of visitors. The reduction in human activity during spring 2020 resulted in a significant increase in the number of breeding pairs at the reservoir (6–7 pairs in years 2015–2019 vs. 15 pairs in year 2020), but the number of breeders on the fishponds did not change significantly (8–11 in years 2015–2019; 10 in year 2020). New territories appeared later at the reservoir in the pandemic year (median laying dates: 8–16 April in 2015–2019; 24 April in 2020). The breeding success of pairs at new locations was very low, with most losing their broods during the fledging period. Nonetheless, the marked change in the year 2020 in the number of Mute Swans breeding at a recreational site suggests that human-related activity may limit the nesting distribution of this species.